2015
DOI: 10.4236/ajibm.2015.53015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tangible and Intangible Rewards on Organizational Commitment: Evidence from the Textile Sector of Pakistan

Abstract: This study explores the relationship between tangible rewards, intangible rewards and organizational commitment with the mediating role of collectivism in the textile sector of Pakistan. In total, 250 questionnaires were distributed. The response rate was 81%. Data were analyzed by using SPSS (20.0) software. Results showed that collectivism was negatively correlated with tangible and intangible rewards and positively correlated with organizational commitment. Further results showed that tangible and intangibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Saeed et al (2013) reported that compensation and job characteristics have a weak positive and significant impact on organisational commitment, but career development has insignificant impact on organisational commitment. Saqib, Abrar, Sabir, Bashir and Baig's (2015) study indicated that there is a relationship between the tangible, intangible rewards and organisational commitment. The empirical results supported the relationship between the tangible rewards and organisational commitment.…”
Section: Discussionmentioning
confidence: 98%
“…Saeed et al (2013) reported that compensation and job characteristics have a weak positive and significant impact on organisational commitment, but career development has insignificant impact on organisational commitment. Saqib, Abrar, Sabir, Bashir and Baig's (2015) study indicated that there is a relationship between the tangible, intangible rewards and organisational commitment. The empirical results supported the relationship between the tangible rewards and organisational commitment.…”
Section: Discussionmentioning
confidence: 98%
“…Material rewards (e.g., money, food) and social rewards (e.g., a smiling face, positive feedback; Demurie, Roeyers, Baeyens & Sonuga-Barke, 2012;Ethridge et al, 2017;Foulkes, Viding, Mccrory & Neumann, 2014) may inspire two different forms of extrinsic motivation. They represent two fundamentally different mechanisms of human motivation (Hansen, Smith & Hansen, 2002;Hussain, Shah & Raza, 2012) and have different effects on human behaviors (Alfandi & Alkahsawneh, 2014;Erbasi & Arat, 2012;Kohls, Peltzer, Herpertz-Dahlmann & Konrad, 2009;Saqib, Abrar, Sabir, Bashir & Baig, 2015;Waqas & Saleem, 2014).…”
Section: Materials and Social Rewardsmentioning
confidence: 99%
“…Job satisfaction is positively affected by tangible incentives and non-financial incentives (Robbins, 2001) [31].Another study conducted in Turkey reported that financial and non-financial incentives are related to job satisfaction (Saqib, S., Abrar, M., Sabir, H.M., Bashir, H., &Baig, S.A., 2015) [32]. Tangible and Intangible incentives lead to more commitment towards job within the textile sector of Pakistan and those who are more committed are more satisfying (Saqib, S., Abrar, M., Sabir, H.M., Bashir, M. and Baig, S.A., 2015) [32].Incentives system encourages the workers and hence they are more satisfied with their job (Scheepers, R., 2009) [33]. Performance and satisfaction is improve as a result of Tangible or intangible incentives(Scheepers, R., 2009) [33].…”
Section: Disscussionmentioning
confidence: 99%